PADUAN VARIASI PUTARAN 0, 250, 550 RPM CENTRIFUGAL CASTING SIFAT FATIK PADUAN A 356 UNTUK VELG SEPEDA MOTOR - M. Abdus Shomad (Teknoin, 2016)
The destination of this research was to determine the effect of rotational speed on the characteristics of fatigue in centrifugal casting alloy A356 aluminum alloy two-wheeled vehicle with a low round and 350 RPM and 550 RPM middle rounds. The casting in this research using a centrifugal casting method. The material used is a cast aluminum alloy A356. Variations rounds used in centrifugal casting is 350 and 550 RPM. Casting process carried out by pre-heating the mold 2500oC, 7500oC casting temperature and with the addition of titanium boron grain refiner 12:08%. Results foundry then made specimen for rotary bending fatigue test in accordance with JIS Z 2274 standard 1. The examination has been done is the rotary bending fatigue test. The examination results showed that the wheels with a round 0 RPM produces a voltage amplitude relationship with the number of cycles Ïƒa = 350 RPM rotation have a relationship with the voltage amplitude and at 550 RPM rotation have a relationship with the voltage amplitude.